MRI cT1–2 rectal cancer staging accuracy: a population-based study. Issue 10 (16th April 2020) - Detering, R; Oostendorp, S E; Meyer, V M; Dieren, S; Bos, A C R K; Dekker, J W T; Reerink, O; Waesberghe, J H T M; Marijnen, C A M; Moons, L M G; Beets-Tan, R G H; Hompes, R; et al.
Abstract: Background: Adequate MRI-based staging of early rectal cancers is essential for decision-making in an era of organ-conserving treatment approaches. The aim of this population-based study was to determine the accuracy of routine daily MRI staging of early rectal cancer, whether or not combined with endorectal ultrasonography (ERUS). Methods: Patients with cT1–2 rectal cancer who underwent local excision or total mesorectal excision (TME) without downsizing (chemo)radiotherapy between 1 January 2011 and 31 December 2018 were selected from the Dutch ColoRectal Audit. The accuracy of imaging was expressed as sensitivity, specificity, and positive predictive value (PPV) and negative predictive value. Results: Of 7382 registered patients with cT1–2 rectal cancer, 5539 were included (5288 MRI alone, 251 MRI and ERUS; 1059 cT1 and 4480 cT2). Among patients with pT1 tumours, 54·7 per cent (792 of 1448) were overstaged by MRI alone, and 31·0 per cent (36 of 116) by MRI and ERUS. Understaging of pT2 disease occurred in 8·2 per cent (197 of 2388) and 27·9 per cent (31 of 111) respectively. MRI alone overstaged pN0 in 17·3 per cent (570 of 3303) and the PPV for assignment of cN0 category was 76·3 per cent (2733 of 3583). Of 834 patients with pT1 N0 disease, potentially suitable for local excision, tumours in 253 patients (30·3 per cent) were staged correctly as cT1 N0, whereas 484 (58·0 per cent) and 97 (11·6 per cent) were overstaged as cT2 N0 and cT1–2 N1 respectively. Conclusion: This Dutch population-based analysis of patients who underwent local excision or TME surgery for cT1–2 rectal cancer based on preoperative MRI staging revealed substantial overstaging, indicating the weaknesses of MRI and missed opportunities for organ preservation strategies. Graphical Abstract: This population-based study determined the accuracy of routine daily MRI staging of early rectal cancer, whether or not combined with endorectal ultrasonography. The results showed that preoperative MRI led to substantial overstaging in patients who underwent local excision or total mesorectal incision surgery for cT1–2 rectal cancer, indicating the weaknesses of MRI and missed opportunities for organ preservation strategies. Imaging weakness